Optimizing handball-specific means to achieve the objectives of physical education and school sports at the 8th grade level - Mihăiţă-Ştefan NICOLAEVICI; Leuciuc Florin Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
Allocating short time to physical education classes in the curriculum, 2 hours per week, for students who do not have inclination and skills, and the short time given covers in a small way the accomplishment of physiological and psychomotor effects, which are necessary for students during school, because they are in a period of growth which extends throughout life. This research, which took place all through the school year during Physical Education and sports classes, shows the increase in motor and somatic indices, which confirms that the proposed means are effective and have led to an optimal development of students who were part of this experiment. Within research, the objectives of physical education are achieved through high indices of physical and motor development, the implementation of a wide range of basic and specific handball skills, the establishment of the habit of practicing physical exercises in students' spare time, the acquisition of new knowledge related to the organization and the progress of the game.